# Integer addition: Problem type 1 Online Quiz

Following quiz provides Multiple Choice Questions (MCQs) related to **Integer addition: Problem type 1**. You will have to read all the given answers and click over the correct answer. If you are not sure about the answer then you can check the answer using **Show Answer** button. You can use **Next Quiz** button to check new set of questions in the quiz.

### Answer : B

### Explanation

**Step 1:**

**Rule:** If the numbers are of opposite signs, find their difference and put the sign of the greater number

**Step 2:**

Difference of [1, 3] = 3 – 1 = 2;

Sign of greater number is –. So, 1 + (−3) = −2

### Answer : C

### Explanation

**Step 1:**

**Rule:** If the numbers are of same sign, we add them and keep the sign on the sum.

**Step 2:**

Sum of [1, 2] = 1 + 2 = 3; Sign of numbers is –.

So, −1 + (−2) = −3

### Answer : A

### Explanation

**Step 1:**

**Rule:** If the numbers are of opposite signs, find their difference and put the sign of the greater number

**Step 2:**

Difference of [3, 3] = 3 – 3 = 0;

So, 3 + (−3) = 0

### Answer : D

### Explanation

**Step 1:**

**Rule:** If the numbers are of same sign, we add them and put their sign on the sum.

**Step 2:**

Sum of [4, 2] = 4 + 2 = 6; Sign of numbers is –.

So, −4 + (−2) = −6

### Answer : A

### Explanation

**Step 1:**

**Rule:** If the numbers are of opposite signs, we find their difference and put the sign of the greater number

**Step 2:**

Difference of [3, 7] = 7 – 3 = 4; Sign of greater number is –.

So, 3 + (−7) = −4

### Answer : C

### Explanation

**Step 1:**

**Rule:** If the numbers are of same sign, we add them and put their sign on the sum.

**Step 2:**

Sum of [4, 6] = 4 + 6 = 10; Sign of numbers is –.

So, −4 + (−6) = −10

### Answer : B

### Explanation

**Step 1:**

**Rule:** If the numbers are of same sign, we add them and put their sign on the sum.

**Step 2:**

Sum of [3, 9] = 9 + 3 = 12; Sign of numbers is –.

So, −3 + (−9) = −12

### Answer : D

### Explanation

**Step 1:**

**Rule:** If the numbers are of opposite signs, we find their difference and put the sign of the greater number.

**Step 2:**

Difference of [5, 2] = 5 – 2 = 3; Sign of greater number is −.

So, 2 + (−5) = −3

### Answer : B

### Explanation

**Step 1:**

**Rule:** If the numbers are of opposite signs, we find their difference and put the sign of the greater number.

**Step 2:**

Difference of [7, 6] = 7 – 6 = 1; Sign of greater number is +.

So, 7 + (−6) = +1 = 1

### Answer : A

### Explanation

**Step 1:**

**Rule:** If the numbers are of same sign, we add them and put their sign on the sum.

**Step 2:**

Sum of [5, 8] = 5 + 8 = 13; Sign of numbers is –.

So, −5 + (−8) = −13